Studi Orientalisme Menurut Sejarah dan Tujuan Gerakannya - Nurachman, Azhar; Mujahid, Kasori (Lembaga Yasin AlSys, 2023)
This article will elaborate in detail on Orientalism from a historical perspective. The study of Orientalism is complex, especially concerning the Orient, particularly Islam, and is driven by motives such as religious, scientific, economic, and political issues. The terms